(untitled) (Research, Society and Development, 2024)
Bruxism is a functional disorder characterized by the involuntary activity of the chewing muscles, constantly and excessively, or when there is rigid movement of the jaw, which can manifest as sleep bruxism and waking bruxism. It has multifactorial etiology, and the use of some drugs is one of these factors. The use and abuse of some substances such as drugs, caffeine, nicotine, alcohol and psychoactive substances are some important variables and agents that can trigger or aggravate bruxism. Drugs, including selective serotonin reuptake inhibitor or selective serotonin or norepinephrine reuptake inhibitors are factors that are involved with the increase or risk of increasing the frequency of bruxism. These medications are used for depression, anxiety and other psychiatric conditions. They can trigger or aggravate the presence of a previous bruxism. The objective of this article is to present a narrative review, to elucidate and collaborate with future work that relates the use of these drugs to bruxism. A search in the databases of the Regional Portal of the Virtual Health Library (BVS Regional), SciELO, PubMed and Google Scholar was established as a search criterion for documents published in the last ten years. The importance of the knowledge of the dentist to diagnose and treat the symptom of this dysfunction, together with the prescribing physician of the inductive medication, is concluded after the research.